2018
DOI: 10.9743/jir.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Your Sanity While Keeping Your Students: How Teacher Engagement Can Increase Student Persistence When Teaching Students During Their First College Course

Abstract: Student persistence is a common concern for online educators. Previous research has shown that student persistence rates are effected by instructor presence, creating a sense of community in the classroom, and varying classroom activities for students (Croxton, 014). Based on the authors' experiences, there Using Web 2.0 tools (Zoom, Loom, Remind, and Flipgrid), increasing discussion board posts containing personal experiences, and using effective time management tools can allow instructors to increase student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Teaching, social, and cognitive presence are dimensions of the Community of Inquiry (CoI) framework, and research has shown that a combination of all three dimensions facilitates student learning in online environments (Garrison, 2017;Edmunds et al, 2021;Richardson et al, 2017). Furthermore, opportunities for online students to engage and interact with their classmates, course materials, and instructor are critical to promoting student persistence (Basko & McCabe, 2018;Kimbark et al, 2017;Stephen, 2022;Stephen, Forthcoming). Hence, certain requirements must be met at the course level to support student persistence.…”
Section: After Admission Internal Factors: Institutional/college/prog...mentioning
confidence: 99%
See 1 more Smart Citation
“…Teaching, social, and cognitive presence are dimensions of the Community of Inquiry (CoI) framework, and research has shown that a combination of all three dimensions facilitates student learning in online environments (Garrison, 2017;Edmunds et al, 2021;Richardson et al, 2017). Furthermore, opportunities for online students to engage and interact with their classmates, course materials, and instructor are critical to promoting student persistence (Basko & McCabe, 2018;Kimbark et al, 2017;Stephen, 2022;Stephen, Forthcoming). Hence, certain requirements must be met at the course level to support student persistence.…”
Section: After Admission Internal Factors: Institutional/college/prog...mentioning
confidence: 99%
“…It is also recommended that online courses incorporate a variety of instructional strategies. Employing various teaching styles and instructional activities can help to address the various learning preferences of nontraditional undergraduate online learners (Basko & McCabe, 2018; Rovai & Downey, 2010). Additionally, online course instructors should solicit anonymous feedback from students, preferably during the mid-point of a course, and again at conclusion, to learn more about students’ learning experiences.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…As emphasized by Basko and McCabe (2018) "…FlipGrid app can maintain students' persistence rates during the teaching-learning process". Moreover, the media can also create a cognitive, social, and teaching presence (Holbeck & Hartman, 2018).…”
mentioning
confidence: 99%